Ratiometric Detection of γ-Glutamyltransferase in Human Colon Cancer Tissues Using a Two-Photon Probe - Kim, Yun Ji; Park, Sang Jun; Lim, Chang Su; Lee, Dong Jun; Noh, Choong Kyun; Lee, Kiyoun; Shin, Sung Jae; Kim, Hwan Myung (Analytical Chemistry, 2019)
γ-Glutamyltransferase (GGT) plays a role in cleaving the γ-glutamyl bond of glutathione. The GGT is known to be overexpressed in some tumors and has been recognized as a potential biomarker for malignant tumors. Colon cancer is one of the most common cancers worldwide; however, there is no quantitative method for detecting cancer cells in human colon tissues. In this study, we report a ratiometric two-photon probe for GGT that can be applied in human colon tissues. The probe (Probe 2) showed high fluorescence efficiency, marked fluorescence changes, excellent kinetics, and selectivity for the GGT in live colon cells. Additionally, we obtained ratiometric two-photon microscopy images of GGT activity in human colon tissue. We used this method to compare normal and cancer tissues based on their ratio values; the ratio value was higher in cancer tissue than in normal tissue. This study provides a method for quantitative analysis of GGT, particularly in human colon cancer, which will be useful for studying GGT-related diseases and diagnosing colon cancer.
Keywords: Fluorescence efficiency; Gamma-glutamyltransferase; Human colon cancer; Malignant tumors; Quantitative method; Ratiometric detection; Two photon microscopy; Two-photon probes